ANALISIS POSITIONING PRODUK BUMBU MASAK INSTANT (STUDI KASUS MEREK : SAJIKU, KOKITA & MAMASUKA) - Islahuddin Daud; Welly Nailis (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2012)
ABSTRACT The Study was conducted to determine perceiptual mapping in instant seasoning. Object of study is the Sajiku, Mamasuka and Royco. This study used a decriptive conclusive research in the form of a single cross-sectional sample of 180 respondents who were in the city of Palembang. Perceptual map is used to see the affinity between the brand and the variables between one brand to another brand. The results of this study have Sajiku brand proximity variable